2008
DOI: 10.1111/j.1741-4520.2008.00179.x
|View full text |Cite
|
Sign up to set email alerts
|

Transplacental transport and tissue distribution of biotin in mice at midgestation

Abstract: Biotin is a water-soluble vitamin which functions as a coenzyme of carboxylases in glucose and amino acid metabolism and fatty acid synthesis. Biotin is also essential for maintaining reproductive function. Biotin deficiency during gestation induces cleft palate, micrognathia and limb hypoplasia in mouse fetuses at near term. Maternal biotin deficiency is severely tetatogenic in mammals. However, the relationship between abnormal morphogenesis and biotin deficiency is not sufficiently clear. This study was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Immediately after fetal echography on E14.5, biotin was injected intravenously into the pregnant dams. To test whether maternal endogenous biotin can cross the placenta and accumulate in fetal tissues, immunofluorescent staining was conducted 51 . In non-immune pregnant mice, biotin crossed the placenta and accumulated in fetal tissues, whereas fetuses from biotin-injected immune mice had less fetal biotin accumulation (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immediately after fetal echography on E14.5, biotin was injected intravenously into the pregnant dams. To test whether maternal endogenous biotin can cross the placenta and accumulate in fetal tissues, immunofluorescent staining was conducted 51 . In non-immune pregnant mice, biotin crossed the placenta and accumulated in fetal tissues, whereas fetuses from biotin-injected immune mice had less fetal biotin accumulation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…After abdominal shaving, chemical depilation (Nair™, Church & Dwight Co, Inc.) and application of coupling gel (37 °C), high-frequency ultrasound imaging was performed by nonlinear contrast imaging using a Vevo ® 2100 system and a MS550 transducer (32–56 MHz). After ultrasound, some animals were intravenously injected with biotin (0.25 g per kg body weight) to test maternal–fetal transport of essential nutrient 51 . Biotin is transported by its sodium-dependent multivitamin transporter 68 .…”
Section: Methodsmentioning
confidence: 99%
“…C. abortus can grow in a number of hosts and tissues, but is best known for causing abortions. Pregnant animals are known to incur transient biotin deficiencies and mouse models have shown that reduced biotin levels in dams correlates with reduced levels of biotin in the fetus [57], [58]. The loss of biotin synthesis by the LLG strain might explain its reduced pathology in a pregnant mouse abortion model and small plaque phenotype and makes it an ideal candidate to test for biotin dependent phenotypes compared to “dual” biotin metabolism C. abortus strains [59].…”
Section: Discussionmentioning
confidence: 99%
“…Detection of holocarboxylase and biotinidase activity. The holocarboxylases (biotinylated carboxylases in vivo) were separated by SDS-PAGE in 8% polyacrylamide gels and detected by Western blotting analysis with streptavidin peroxidase (11,28,35).…”
Section: Animals and Dietsmentioning
confidence: 99%
“…In experimental animals, biotin deficiency has been demonstrated to have teratogenic effects (e.g. cleft palate, micrognathia, and micromelia) in mice (7)(8)(9)(10)(11)(12)(13)(14). Biotin deficiency also causes metabolic disorders, for example, increased urinary excretion of 3-hydroxyisovaleric acid (3-HIA) due to decreased MCC activity (15).…”
mentioning
confidence: 99%